The effects of digital literacy and product innovation on MSME marketing performance: The mediating role of digital marketing - Feby Evelyna; Siti Nur Azizah (Institute of Accounting Research and Novation (IARN), 2026)
This study addressed the inconsistent findings and empirical gaps regarding the factors influencing micro, small, and medium enterprises (MSMEs) marketing performance. The investigation examined the direct effects of digital literacy and product innovation on marketing performance, alongside the mediating role of digital marketing. A quantitative approach was deployed, using purposive sampling to collect data from 140 MSME owners in Kebumen Regency who utilized digital applications. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The results revealed that digital literacy and product innovation exerted positive and significant direct impacts on both digital marketing and marketing performance. Furthermore, the structural model analysis confirmed that digital marketing successfully mediated the relationships between digital literacy, product innovation, and marketing performance. Major findings indicated that technological readiness and product innovation yielded optimal contributions to business performance when executed through structured digital marketing platforms. Consequently, this study concluded that enhancing digital marketing strategies serves as a vital mechanism for MSMEs to leverage their digital capabilities and innovative products effectively to maximize market reach and boost overall marketing performance